(3eUfa GHf CHj TjHIs - (3CHh HcQ YHO Gddg Hf eMeO Hf CHj TjHI GdYHSj, GHf CHj TjHI,J (B235 (3g` s
(3ChdgG (B:s
(3jHJOC HChd cJGH GdfcGM s
(3BNQgG (B:s
(3jfJgi HBNQ cJGH GdWdGb s
(3GdLRA GdSGHY ef fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B117s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1711s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI eQGO edG (B(592( (3L(B)) s
Keywords: (3GdMOjK h GdeUWdMs